Thermal Transport in Sheared Nanoparticle Suspensions: Effect of Temperature. Issue 16 (2nd October 2019) - Sun, Chengzhen; Bai, Bofeng; Lu, Wen-Qiang
ABSTRACT: Nanoparticle suspensions, known as nanofluids, exhibit many potential applications in thermal and chemical engineering, of which the thermal transport characteristics have a great dependence with the corresponding flow process and heat transfer process. Recently, a shear flow-induced enhancement of the thermal transport in the nanoparticle suspensions was previously reported. Here, the effective thermal conductivity (ETC) of deionized water based silicon oxide nanoparticle suspensions in the shear flows at different temperatures were experimentally measured to elucidate the effect of temperature on the thermal transport in sheared nanoparticle suspensions. The results show that the ETC enhancement induced by shear flows is more obvious at lower temperatures, which can be attributed to the easily formed nanoparticle agglomerates for the lower mobilities of nanoparticles. Meanwhile, a correlation for quantitatively predicting the ETC enhancements, i.e., the ratios of infinite-shear thermal conductivity to zero-shear thermal conductivity, is proposed with considering the effect of temperature. In summary, the thermal transport in sheared nanoparticle suspensions demonstrates distinctive characteristics at different temperatures for the distinguishing nanoparticle structures.